Pediatric applications of endoscopic spine surgery - Ankush Bajaj, BS; Albert E. Telfeian, MD, PhD (Interdisciplinary Neurosurgery, 2022)
Minimally invasive approaches to spinal pathology have progressed through the advent of navigation and high-definition endoscopes. Endoscopic spine surgery affords key advantages for operative visualization and is associated with reduced tissue trauma and complication rates relative to open surgery. The excellent functional outcomes and expedient postoperative recovery afforded by endoscopic approaches is of great benefit to children and adolescents, whose quality of life can be drastically impacted by postoperative complications and revision surgeries. In this chapter, we discuss the applications and advantages of pediatric endoscopic spine surgery and detail our experiences with two case examples: (1) transforaminal endoscopic discectomy for pediatric lumbar disc herniation and (2) endoscopic approaches for thoracic spinal tumor resection.